Fatal risk : a cautionary tale of AIG's corporate suicide - Boyd, Roddy, 1968- (Hoboken, N.J. : Wiley, 2011)
'The true story of how risk destroys, as told through the ongoing saga of AIG. From the collapse of Bear Stearns and Lehman Brothers, the subject of the financial crisis has been well covered. However, the story central to the crisis-that of AIG-has until now remained largely untold. Fatal Risk: A Cautionary Tale of AIG's Corporate Suicide tells the inside story of what really went on inside AIG that caused it to choke on risk and nearly bringing down the entire economic system. The book reveals inside information available nowhere else, including the personal notes and records of key players such as the former Chairman of AIG, Hank Greenberg. Takes readers behind the scenes at the U.S. Treasury and the Federal Reserve Bank of New York. Details how an understanding of risk built AIG, but a disdain for government regulators led to a run-in with New York State Attorney General Eliot Spitzer. Fatal Risk is the comprehensive and compelling true story of the company at the center of the financial storm and how it nearly caused the entire economic system to collapse.'--
Includes bibliographical references and index.
Keywords: American International Group, Inc. -- History; Insurance companies -- United States -- History; Federal aid -- United States; Financial crises -- United States; Global Financial Crisis, 2008-2009.